Retrospective Case Analysis on the Effectiveness of Boerhavia Diffusa Mother Tincture in the Management of Essential Hypertension (Advancements in Homeopathic Research, 2024)
Background: Hypertension is a prevalent medical  condition with significant health implications.  This retrospective case record analysis aimed to  investigate the efficacy of Boerhaavia diffusa mother  tincture in managing hypertension. The study utilized  data from diverse healthcare settings affiliated with  Sivaraj Homoeopathic Medical College and Research  Institute, Salem. Methods: A total of 30 cases meeting the inclusion  criteria, comprising both sexes aged between 30 to 75  years, diagnosed with hypertension based on clinical  parameters (systolic BP >140 mmHg, diastolic BP  >90 mmHg), and presenting common symptoms,  were included. Exclusion criteria encompassed cases  of secondary hypertension and those with incomplete  follow-ups. The efficacy of Boerhaavia diffusa  mother tincture was assessed by changes in blood  pressure recorded during the treatment period. The  study adhered to ethical guidelines, and all patients  received Boerhaavia diffusa mother tincture as part  of their therapeutic regimen. Results and Discussion: Among the 30 cases  analyzed, 6 patients exhibited marked improvement,  10 demonstrated moderate improvement, and 10  showed mild improvement, while 4 cases showed  no improvement. Notably, the majority of patients  experienced marked symptomatic relief. Despite the  positive trend observed in the outcomes, the study  has limitations, including a small sample size and  the absence of a control group. The lack of detailed information on dosage and treatment duration  further restricts the generalizability of the findings.  The retrospective nature of the analysis introduces  potential biases, and confounding factors such as  lifestyle changes were not systematically addressed. Conclusion: This retrospective case record analysis  suggests a potential beneficial effect of Boerhaavia  diffusa mother tincture in managing hypertension.  The majority of patients experienced symptomatic  relief, although caution is warranted due to study  limitations. Future research, including well-designed  randomized controlled trials with larger sample  sizes, is needed to establish the efficacy and safety  of Boerhaavia diffusa mother tincture in hypertensive  patients.
Keywords: Boerhavia Diffusa; Hypertension; Homoeopathy